Malaysian literature and its future: an interview with Muhammad Haji Salleh - Ahmad Safian, Nursafira; Quayum, Mohammad Abdul (IIUM, 2019)
This interview was conducted in Prof. Muhammad’s office room at the Kulliyyah of Islamic Revealed Knowledge and Human Sciences, IIUM, on 18 September 2018. It has since been transcribed, revised and edited to bring it to a publishable form. The interview covers a wide spectrum of issues, ranging from Muhammad’s creative and personal life, to the importance of translation and the future of Malaysian literature with the country’s changing political circumstance. It also investigates Muhammad’s views on Malay culture, the unique aspects of Malay and Malaysianess, the role of the writer in shaping the Malaysian national identity, the relationship between history and literature, Muhammad’s views about English and Malaysian writings in the English language and his advice for budding writers in Malaysia and especially those in the Malay language. The interview further delves into Muhammad’s creative process, how travelling has benefitted his poetic growth, his impression of the Arab writers and the relationship between literature and religion; how Muhammad negotiates between his creative and critical self, how to improve the standing of literature and especially the National Laureates in the New Malaysia, what awards mean to him and, finally, what he is writing now and what are his future plans as a poet and Malaysia’s leading literary elderstatesman.